Narrative skills of Polish bilingual six-year-old children. A case study - Młyński, Rafał; Guzek, Agata; Murzyn, Magdalena; Olszewska, Julia; Starzec, Natalia (Papers in Linguistics, 2026)
The aim of the article is to present the narrative competence of five bilingual, neurotypical six-year-old children whose intellectual development is within the norm. The study focused on them independently producing a narrative based on a six-picture story. Language samples were collected in both Polish and English, using the Multilingual Assessment Instrument for Narratives (MAIN). Macrostructural analysis of the narratives was conducted in accordance with the MAIN authors’ guidelines and included the presence of such elements as: introduction, initiating mental state, goal, attempt, outcome, and final mental state. Microstructural analysis was based on the theoretical framework proposed by Stanisław Grabias, Tomasz Woźniak, and Marek Kurkowski, encompassing narrative fluency, phonological sequencing, grammatical competence, and lexical competence. In addition, the children’s ability to linguistically express mental states of the story characters was assessed. The results point to similar macro- and microstructural features in the narratives produced in Polish and English. At the same time, the children had difficulties in linguistically expressing the characters’ mental states. These findings were interpreted in the light of current literature on speech therapy, which helped to formulate application-oriented conclusions relevant to the development of narrative competence, particularly in Polish as a heritage language.